Comparing optical deposition and drop casting for enhanced tunability in Q-switched fiber lasers using a biogenic AgNPs-CS saturable absorber - Zalkepali, N U H H; Awang, N A; Zamri, A Z M; Mahmud, N N H E N; Mun, K L (iop, 2024)
This study presents the successful synthesis and characterization of silver nanoparticles(AgNPs) using Camellia sinensis(CS)leaf extract as a biogenic saturable absorber(SA) for tunable Q-switched applications. The AgNPs-CS SA was fabricated through optical deposition and drop casting methods into a fiber ferrule. The nonlinear optical properties of AgNPs-CS as SA were investigated, revealing a modulation depth of 24.37% and a saturation intensity of 0.15 MW cm−2 . Q-switching based on optical deposition exhibited a pump power of 213.40 mW, a 3-dB bandwidth of 3.20 nm, a pulse repetition rate of 78.74 kHz, and a pulse duration of 2.38 μs. Meanwhile, the drop casting method showed a 3-dB bandwidth of 2.0 nm, a pulse repetition rate of 53.05 kHz, and a pulse duration of 5.53 μs for the Q-switched pulse. Additionally, the tunability of wavelength in Q-switching using AgNPsCS SA was investigated. The drop casting method achieved a tuning range of 32.00 nm, covering the S-band to C-band, while the optical deposition technique resulted in a tuning range of 54.20 nm, spanning from the C-band to L-band. Notably, this work represents the first utilization of AgNPs synthesized with leaf extract as a biogenic SA in the tunability of Q-switched lasers, employing two distinct fabrication techniques for the SA.